Growth velocity increase in children with Turner syndrome treated with growth hormone following a brief therapy interruption - Andrzej Kędzia; Katarzyna Anna Majewska (Termedia Publishing House, 2023)
Growth failure is a substantial feature of Turner syndrome (TS) and typically progresses from infancy to adulthood. Proper growth hormone (GH) treatment in TS is essential to increase growth velocity and improve the final height. The aim of the study was to perform a preliminary assessment of the influence of short interruptions in GH therapy on the growth process in children with TS. Growth velocities were analyzed in 5 patients with TS, treated long term with GH, who experienced short breaks in drug administration, followed by the re-introduction of treatment. The average growth velocity after the treatment interruption increased 2-fold compared to the continuous therapy and 1.3/1.5-fold compared to the period of initial GH therapy. The results suggest that the catch-up growth typical for the beginning of the GH therapy is not a single phenomenon and may recur in TS children in the case of re-introduction treatment after a short interruption.